Emergency department point-of-care ultrasound in out-of-hospital and in-ED cardiac arrest. (December 2016) - Gaspari, Romolo; Weekes, Anthony; Adhikari, Srikar; Noble, Vicki E.; Nomura, Jason T.; Theodoro, Daniel; Woo, Michael; Atkinson, Paul; Blehar, David; Brown, Samuel M.; Caffery, Terrell; Douglass, Emily; et al.
Abstract: Background: Point-of-care ultrasound has been suggested to improve outcomes from advanced cardiac life support (ACLS), but no large studies have explored how it should be incorporated into ACLS. Our aim was to determine whether cardiac activity on ultrasound during ACLS is associated with improved survival. Methods: We conducted a non-randomized, prospective, protocol-driven observational study at 20 hospitals across United States and Canada. Patients presenting with out-of-hospital arrest or in-ED arrest with pulseless electrical activity or asystole were included. An ultrasound was performed at the beginning and end of ACLS. The primary outcome was survival to hospital admission. Secondary outcomes included survival to hospital discharge and return of spontaneous circulation. Findings: 793 patients were enrolled, 208 (26.2%) survived the initial resuscitation, 114 (14.4%) survived to hospital admission, and 13 (1.6%) survived to hospital discharge. Cardiac activity on US was the variable most associated with survival at all time points. On multivariate regression modeling, cardiac activity was associated with increased survival to hospital admission (OR 3.6, 2.2–5.9) and hospital discharge (OR 5.7, 1.5–21.9). No cardiac activity on US was associated with non-survival, but 0.6% (95% CI 0.3–2.3) survived to discharge. Ultrasound identified findings that responded to non-ACLS interventions. Patients with pericardial effusion and pericardiocentesis demonstrated higher survival rates (15.4%) compared to all others (1.3%). Conclusion: Cardiac activity on ultrasound was the variable most associated with survival following cardiac arrest. Ultrasound during cardiac arrest identifies interventions outside of the standard ACLS algorithm.